ʼA mhatʻ ta ra Joʻgyī (Tuiṅʻʺ Laṅʻʺ Cā pe, 1999)
On the life and works of Joʻgyī, b. 1908, Burmese writer; contributed articles brought out on his 9th death anniversary On the life and works of Joʿgyī, b. 1908, Burmese writer; contributed articles brought out on his 9th death anniversary
Keywords: Joʻgyī